Evolution of the Earth's magnetic field strength in northwestern Argentina during the last two millennia: Towards the improvement of south American geomagnetic paleosecular variation curve. (June 2023) - Goguitchaichvili, Avto; García-Ruiz, Rafael; Greco, Catriel; Kravchinsky, Vadim; Rodríguez, Nayeli Pérez; Morales, Juan; Berkovich, Cesar
Abstract: A magnetic mineralogy and absolute geomagnetic intensity study was carried out on prehispanic ceramic fragments from the Southern Andes region (Northwest Argentina). Magnetic susceptibility vs. temperature curves and alternating field demagnetization treatments were applied to select the most suitable samples for the absolute archaeointensity experiments. A total of 66 samples were analyzed following the Thellier modified by Coe protocol, including cooling rate corrections and potential mitigation of the magnetic anisotropy effect. Thirty-eight samples (out of 66) belonging to nine pottery fragments yielded reliable absolute intensity determinations The new data, accompanied by associated radiocarbon ages, were integrated into previously published data in order to construct an improved paleosecular variation curve for South America. The highest quality data covers only the last 1000 years. The general variation patterns show good agreement with global geomagnetic prediction models. This updated regional curve may be used as the reference curve for archaeomagnetic dating in the major part of South America (Brazil, Argentina, Chile, Uruguay and Bolivia), even though caution should be paid for the areas and time periods poorly covered by data. Highlights: A detailed magnetic, mineralogy and absolute geomagnetic intensity study was carried out from Northwest Argentina. Thirty-Eight specimens yielded technically acceptable paleointensity determinations based on their quality factors. These data are distributed between 1606 BP and 416 BP. The regional curve may be used as the most reliable archaeomagnetic dating tool for the major part of South America.